2015
DOI: 10.2149/tmh.2014-19
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-seeking Paths in the Management of Severe Malaria in Children under 15 Years of Age Treated in Reference Hospitals of Kinshasa, Democratic Republic of Congo

Abstract: Background: In the Democratic Republic of Congo (DRC), few studies have focused on treatment-seeking paths selected by caretakers for the management of severe childhood malaria in an urban environment. The present study aims at describing the treatment-seeking paths according to the characteristics of households, as well as the subsequent impact on pre-hospitalisation delay and malarial fatality and on the main syndromes associated with severe childhood malaria. Methods: This descriptive study included data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Prior studies have shown inconsistent results regarding the impact of delayed care seeking on severe malaria risk. [6][7][8][9] These studies demonstrated association between longer duration of symptoms or arbitrarily set cut-offs defining duration of symptoms before admission and severe malaria, but they did not consider the standard WHO definition of delay and severe malaria risk. One study conducted in the Gambia showed lack of association between duration of symptoms and severe malaria, a finding attributed to difficulties in recollection of accurate historical information by distressed mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown inconsistent results regarding the impact of delayed care seeking on severe malaria risk. [6][7][8][9] These studies demonstrated association between longer duration of symptoms or arbitrarily set cut-offs defining duration of symptoms before admission and severe malaria, but they did not consider the standard WHO definition of delay and severe malaria risk. One study conducted in the Gambia showed lack of association between duration of symptoms and severe malaria, a finding attributed to difficulties in recollection of accurate historical information by distressed mothers.…”
Section: Discussionmentioning
confidence: 99%
“…4 This strategy is logical as progression to severe disease requires extensive parasite multiplication over time. 5 Support for delayed care seeking as a risk factor for severe malaria is largely based on results from cross-sectional studies demonstrating association between longer duration of symptoms and severe malaria [6][7][8][9] and demonstration of rapid progression of uncomplicated to severe malaria. 10,11 However, some studies have not shown an association between duration of symptoms and risk of severe malaria.…”
Section: Introductionmentioning
confidence: 99%
“…In the language of economics, these are constraints and preferences, respectively [ 53 ]. Inaccessibility to health facilities due to high costs, distance, and lack of transportation represents the most common constraint to formal healthcare seeking in both the northern and the southern regions of Nigeria [ 54 , 55 ]. On the other hand, the most frequent barriers (preferences) in this study were ignorance of the severity of the child’s illness and use of traditional care in lieu of formal care.…”
Section: Discussionmentioning
confidence: 99%
“…Potential covariates were identified for inclusion in a predictive model using a review of the literature for ‘treatment-seeking’ and ‘care-seeking’ for both ‘malaria’ and ‘fever’ in PubMed on 18 July 2015 [ 31 ]. The following have been reported as determinants of care-seeking rates: household wealth [ 15 , 17 , 19 , 20 , 22 , 32 – 38 ], care-giver education [ 15 , 19 , 32 , 34 , 39 ] and household location (rural or urban) or access to health facilities [ 15 , 20 22 , 32 , 33 , 40 – 45 ]. The World Bank provides freely available national-level indicator data [ 46 ], and several indicators that were in keeping with the themes identified by the literature were downloaded: access to electricity (as a proxy for wealth and access to health facilities), gross domestic product (GDP; current US$), GDP per capita, GDP growth (annual %), gross national income (GNI) per capita (current US$), total health expenditure (% of GDP), public health expenditure (% of total), primary education completion rate (% of relevant age group), and rural population (% of total population).…”
Section: Methodsmentioning
confidence: 99%